Violencia y Salud mental - Saavedra-Castillo, Alfredo (2004)
The author reviews the relationship between violence and mental health. Initially, a review about general concepts of violence is made in order to place oneself into a macrosocial perspective. Subsequently, the concept of violence and citizenshipsecurity is developed, presenting a national survey about psychosocial problems that are mainly related to citizenship security in which alcoholism and drug addiction are placed among first causes. Such findings are below analysed by regions where the problem concerning drugs and street and social violence areclosely connected. Afterwards, the extent of drug dependence is shown considering it one of the most significant ways of social violence, providing specific number about people affected. Likewise, studies about diverse antisocial behaviors anddrug use are most specifically developed with emphasis on alcohol and cocaine derivatives, stating such behaviors are mostly prevalent ones. Later, the author reviews the relationship between violent behaviors and mental health seen fromthe national and international epidemiological studies so that it is evident, on one side, the high involvement of alcohol and drugs in the explanation of a violent behavior and also the strong relationship of these with other mental health pathologies like psychosis, brain organic disorders and several personalitydisorders. A reference to the studies about criminal behaviors and judicial system is also provided below with a review of the relationship between crimes and substance use. Subsequently, a review about domestic violence is made in which children abuse and its relationship with parental substance abuse, strong parentalpersonality pathology and maltreatment in childhood are emphasized. A review about etiological factors of violence and drug use from a biopsychosocial perspective with an emphasis on most remarkable data of each, but making evident many confluences in etiological factors of both conditions. Finally, aconceptualization of antisocial personality is made to analyse then its relation to drug use and several considerations about differential diagnosis.